Pertanggungjawaban Pidana Pelaku Tindak Pidana Korupsi Dana Hibah Pengadaan Bibit Sapi (Studi Putusan Nomor 1/Pid.Sus-TPK/2019/PN Dps) - I Kadek Edy Sanjaya; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Jurnal Preferensi Hukum, 2020)
This study aims to analyze the "Criminal Accountability of Corruption Actors in Grants for Beef Procurement Grants". Legal issues arising from this study include: How is the arrangement of grants and their relationship with criminal acts of corruption, as well as criminal liability for perpetrators of corruption in the procurement of cattle (Decision Number 1/PPid. Sus-TPK/2019/PN Dps). The research method used in this research is normative legal research with statutory, conceptual and case approaches. Based on the results of this study, it can be concluded several things: 1) Grant arrangements are regulated in Article 1666, 1682 and 1682 of the Civil Code; 2) The relationship between grants and corruption related to grants is a wet field that is used by individuals to commit corruption. 3) Based on Decision Number 1 / Pid.Sus-TPK / 2019 / PN Dps, the defendant is proven to have violated Article 3 in conjunction with Article 18 of Law Number 31 of 1999 concerning Eradication of Corruption Crimes in conjunction with Law Number 20 of 2002. Form of criminal liability the perpetrators of corruption in the form of imprisonment for 2 (two) years and 4 (four) months minus the temporary detention period and based on orders so that the defendant remains in custody and a fine of Rp 50,000,000 (fifty million rupiah) subsidair 2 (two) a month of confinement, and is charged to pay a replacement money of Rp 127,350,000 (one hundred twenty seven million three hundred fifty thousand rupiah). The advice that can be given to the reader is through education and exemplary attitude from the leader who becomes the main spear as a reflection of the government towards the next generation. For further researchers who will examine the crime of corruption in order to dig deeper about how the government plays a role in efforts to prevent corruption